Analisis Pengalamam Pelaku UMKM Jasa Mua Dalam Implementasi Strategi Pemasaran Digital - Karen Nibenia Hia; Lulu Permatasari; Winni Gressia Raja Gukguk; Pupung Purnama Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the experiences of Micro, Small, and Medium Enterprises (MSMEs) providing Make-Up Artist (MUA) services in Bekasi Regency in implementing digital marketing strategies. This study aims to reveal the challenges, opportunities, and impacts of using digital marketing strategies on their business success. A qualitative research method with a case study approach was used, involving in-depth interviews with a number of MUA service MSMEs in Bekasi Regency. The research results are expected to provide a comprehensive overview of the effectiveness of digital marketing strategies for MUA service MSMEs in the region, as well as their implications for the development of more effective business policies and strategies in the future. This research contributes to a better understanding of the application of digital marketing strategies in the context of beauty service MSMEs in Indonesia, specifically in Bekasi Regency.